ATTITUDES TOWARDS THE ELDERLY AMONG TURKISH PHARMACY STUDENTS - (:unkn) unknown (GUNES KITABEVI LTD STI, 2015)
Introduction: The number of elderly people as a proportion of the total population is rapidly increasing, and they have the greatest need for healthcare services, including pharmaceutical care. Therefore, development of positive attitudes and behaviour regarding elderly people and ageing is particularly important for pharmacists. This cross-sectional study evaluated the attitudes of second-year pharmacy students at two Turkish universities on elderly. Materials and Method: Self-administered questionnaires completed by 277 students collected sociodemographic information and responses to the University of California, Los Angeles Geriatrics Attitudes Scale (UCLA), which has been validated in Turkish. Results: The average score on this scale was 47.23 +/- 5.93. Female students had significantly more positive attitudes than males. Personal variables such as previous experience in offering services to the elderly or living with an elderly relative and having an elderly relative did not significantly affect the attitudes towards the elderly. Conclusion: It is recommended that pharmacy schools expand their coverage of healthcare for the elderly in order to facilitate development of relevant knowledge and positive attitudes towards this population.
Keywords: Attitudes Towards the Elderly; Students; Pharmacy; OLDER-PEOPLE; MEDICAL-STUDENTS; KNOWLEDGE; GERIATRICS; EDUCATION; CARE; IMPACT